The Handling and Composition of Purse Seine Catches at Fishing Port, Batam City - Raja Rijik; Robet Perangin-angin; Nasruddin; Eli Nurlaela (Yayasan Serumpun Karang Konservasi, 2023)
Handling fish on board must be carried out properly to maintain the quality of the fish obtained. This study analyzed the handling process and composition of catches on purse seine vessels unloaded at the Fishing Port, Batam City. Handling of catches on purse seine vessels is carried out in the following stages, namely loading fish onto the ship, washing fish, sorting fish, washing fish before entering the Air Blasting Freezer (ABF) room, freezing using Air Blasting Freezer (ABF), packaging, and storage in cold storage rooms. The catch on trip 1st, with fishing operations from March 21st to April 15th 2022, resulted in a catch of 36,308 kg, with the following percentage of dominant catch composition, namely Indian scad of 78.61%, Bigeye scad of 7 .52%, Shrimp scad of 3.41%, Yellowtail scad of 3.05%, and Indian mackerel of 2.63%. The catch on trip 2nd, during the fishing operation period, from April 21st to May 13th, 2022, is presented in Table 2. The catch consisted of target and non-target species, with a total weight of 21,386 kg. The catch was dominated by Indian scad of 80.47%, Bigeye scad of 5.81%, Goldstripe sardinella of 5.29%, Bullet tuna of 2.63%, and Squid of 2.14%. Indian scad is the dominant species caught in the purse seine operation.